EKSPERIMENTASI MODEL PEMBELAJARAN INQUIRY LEARNING DAN DISCOVERY LEARNING TERHADAP PRESTASI BELAJAR DAN KEMAMPUAN KOMUNIKASI MATEMATIS PADA MATERI BANGUN RUANG SISI DATAR DITINJAU DARI KECERDASAN SPASIAL SISWA KELAS VIII SMP NEGERI SE-KOTA SURAKARTA - Aziz, Abdul; Budiyono, Budiyono; Subanti, Sri (Journal of Mathematics and Mathematics Education, 2015)
Abstract: The purpose of this research was to know the effect of the learning models on the learning achievement and mathematics communication ability viewed from the spatial quotient. The learning models compared were Inquiry learning, Discovery learning and Classical model. The type of this study was a quasi-experimental study with a 3 x 3 factorial design. The study population was all grade VIII students of Junior High School in Solo city. Sample was collected by stratified cluster random sampling and consisted of 260 students which where divided into three groups,  86 students in Experimental Group 1, 86 students in Experimental Group 2, and 88 students in Control Group . The instruments of the research include mathematics achievement test, mathematics communication ability test and spatial intelligence test. The technique of analyzing data used the two-way multivariate analysis of variance with unbalanced cell. The results of this research could be concluded as follows ,  (1) Inquiry Learning and Discovery Learning have better learning achievement and mathematics communication ability aspects than the Classical learning, Besides that, Inquiry Learning and Discovery Learning  have the same learning achievement and mathematics communication ability; (2) The students with high spatial intelligence have the same learning achievement and mathematics communication ability as middle spatial intelligence. In addition, students who have high and middle spatial intelligence have better learning achievement and mathematics communication ability than students who have low spatial intelligence.; (3) In each learning model, the students with high and middle spatial intelligence have better learning achievement and mathematics communication ability than students who have low spatial intelligence, and the students with high and middle spatial intelligence have the same learning achievement and mathematics communication ability; (4) In each of the spatial intelligence, the cooperative learning model of Inquiry Learning and Discovery Learning give a better learning achievement and mathematics communication ability than the Classical model, and the cooperative learning model of Inquiry Learning and Discovery Learning give the same learning achievement and mathematics communication ability.Keywords: Inquiry Learning, Discovery Learning, Spatial Quotient, Learning Achievement, Mathematics Communication Ability.